The Effect Of Reproductive Health Education Contextual Learning Methods In The Use Of Gadgets On Risky Sexual Behavior In Adolescent Girls In High School Medan Family Education Foundation In 2022 - Handayani, Purnama; Sunartono, Sunartono; Mediastuti, Fitriani (Jurnal EduHealth, 2023)
The increase in the use of gadgets causes various changes in behavior and attitudes among adolescents. Teenagers are highly susceptible to certain applications on gadgets that eventually lead to risky sexual behaviours. Gadget abuse can have a detrimental impact on the quality of adolescents' lives, so it needs to be addressed. Therefore, there is a need for education in the use of gadgets to prevent risky sexual behaviours in adolescents. The research objective is to determine the effect of contextual reproductive health education methods on the use of gadgets in reducing risky sexual behaviours among adolescent girls. This research follows a pre-experimental design with a one-group pre-post-test approach and was conducted at the Medan Family Education Foundation High School from April 10 to May 5, 2023. The population of this study consisted of 164 individuals, with a sample of 40 participants selected using purposive sampling. Data analysis was performed using univariate and bivariate paired t-tests. The results of this study show that contextual reproductive health education methods in the use of gadgets have an influence on risky sexual behaviours among adolescent girls, covering three domains: knowledge (pre-test with a mean of 4.2750 and post-test with a mean of 6.8750, resulting in an increase difference of 2.6 with a p-value of 0.000), attitude (pre-test with a mean of 22.4500 and post-test with a mean of 31.3500, resulting in an increase difference of 8.9 with a p-value of 0.000), and action (pre-test with a mean of 26.2250 and post-test with a mean of 22.2750, resulting in a difference of 3.95 with a p-value of 0.000) Reproductive health education provided to adolescents through contextual learning methods can improve risky sexual behavior from the impact of sexual content.